Demonologia w Sermones św. Piotra Chryzologa - Kochaniewicz, Bogusław (Poznańskie Studia Teologiczne, 2020)
The article presents the role of evil spirits in the history of salvation according to Saint Peter Chrysologus. This argument has not been examined so far though it is to be found in many homilies of the Bishop of Ravenna. His sermons explain the reason for the fall of the angels created by God as wonderful heavenly beings. They explain the devil’s role in temptation, indicating the cause of evil to the world. The preacher emphasizes the victory of Christ over Satan and points to him as a source of hope for Christians in their spiritual struggle, in which practice of prayer and fasting are helpful.